Facile and diastereoselective synthesis of 3, 2′-spiropyrrolidine-oxindoles derivatives, their molecular docking and antiproliferative activities. Issue 2 (15th January 2015) - Kathirvelan, D.; Haribabu, J.; Reddy, B.S.R.; Balachandran, C.; Duraipandiyan, V.
Graphical abstract: Abstract: In the present study, a series of novel highly functionalized spiropyrrolidine–oxindoles have been synthesized through 1, 3-dipolar cycloaddition of an azomethine ylide formed from isatin and various amino acids such as sarcosine, proline and thioproline with the dipolarophile ( E )-3-(1, 3-diphenyl-1H-pyrazol-4-yl)-2-(1H-indole-3-carbonyl)acrylonitrile under optimized conditions. All the synthesized compounds were evaluated for their antimicrobial activity and shown significant activity.